Grasslands and Herbivore Production in Europe and Effects of Common Policies (Éditions Quæ, 2021)
The European project Multisward ( http://www.multisward.eu/multisward_eng/ ) aims at supporting developments and innovations in grassland use and management in different European farming systems (including low-input and organic farming systems), pedoclimatic and socio-economic conditions i) to enhance the role of grasslands at farm and landscape levels to produce environmental goods and to limit the erosion of biodiversity and ii) to optimise economic, agronomic and nutritional advantages for the development of innovative and sustainable ruminant production systems. The identification of the innovations and their implementation required an exhaustive analysis of the state of grasslands and herbivore production in Europe including how they changed over decades. The effects of public policies were investigated. The results of this analysis are published in the present book.